Streptococcal Infection as a Major Historical Cause of Stuttering: Data, Mechanisms, and Current Importance - Alm, Per A. (Frontiers in Human Neuroscience, 2020)
Stuttering is one of the most well-known speech disorders, but the underlying neurological mechanisms are debated. In addition to genetic factors there are also major non-genetic contributions. It is here proposed that infection with group A beta-hemolytic streptococcus (GAS) was a major underlying cause of stuttering until the mid 1900s, when penicillin was introduced for the treatment of streptococcal infections about 1946. The main mechanism proposed is an autoimmune reaction from tonsillitis, targeting specific molecules, for example within the basal ganglia. It is here also proposed that GAS infections may have continued to cause stuttering to some extent, to the present date, though more rarely. If so, early diagnosis of such cases would be of importance. Childhood cases with sudden onset of stuttering after throat infection may be particularly important to assess for possible GAS infection. The support for this hypothesis primarily comes from three lines of argument. First, medical record data from the 1930s strongly indicates that there was one type of medical event in particular that preceded the onset of childhood stuttering with unexpected frequency: diseases related to GAS throat infections. In particular, this included tonsillitis and scarlet fever, but also rheumatic fever. Rheumatic fever is a childhood autoimmune sequela of GAS infection, which was a relatively widespread medical problem until the early 1960s. Secondly, available reports of changes of the childhood prevalence of stuttering indicates striking parallels between stuttering and the incidence of rheumatic fever, with (1) decline from the early 1900s, (2) marked decline from the introduction of penicillin about 1946, and (3) reaching a more stable level in the 1960s. The correlations between the data for stuttering and for rheumatic fever after introduction of penicillin are very high, at about 0.95. Thirdly, there are established biological mechanisms linking GAS tonsillitis to immunological effects on the brain. In addition, a small number of more recent case reports have provided further support for the hypothesis linking stuttering to GAS infection. Overall, it is proposed that the available data provides strong evidence for the hypothesis that GAS infection was a major cause of stuttering until the mid 1900s.